A solvent-free solid catalyst for the selective and color-indicating ambient-air removal of sulfur mustard - Daniel L. Collins-Wildman (Nature Portfolio, 2021)
Decontamination of sulfur-containing chemical warfare agents can be achieved through selective, air-based oxidation. Here a solid, solvent-free catalyst for aerobic oxidative decontamination of sulfur mustard is reported.